Tolu Dance in The Senggighilang Art Studio, Bailang Village, Bunaken District, Manado City - Apriliani Marsella Debora Moray; Kompiang Gede Widyana; Suminto (Jurnal IGEL : Journal Of Dance, 2025)
Higher education in Indonesia aims to produce quality graduates through the Merdeka Belajar Kampus Merdeka program, but the implementation of this program still faces a number of challenges, especially in the lack of dance literacy, especially in North Sulawesi. This study aims to analyze the elements and symbolic meanings contained in the Tolu dance performance: Our Appreciation for You at the Senggighilang Art Studio. This study uses a qualitative descriptive approach, with aesthetic theory and semiotic theory dance literacy, especially in North Sulawesi. This study aims to analyze the elements and symbolic meanings containedin the Tolu dance performance: Our Appreciation for You at the Senggighilang Art Studio. This study uses a qualitativedescriptive approach, with aesthetic theory and semiotic theory.The data collection process goes through the stages of observation, interviews, documentation and data